Comparison of mental fatigue using EEG signals and task performance in normal and slump posture adults during computer typing. - Abdollahzade, Zahra; Hadian, Mohammad Reza; Talebian, Saeed; Khanmohammadi, Roya; Sarfraz, Muhammad (Journal of Bodywork & Movement Therapies, 2024)
Slump sitting at workstations has been focused on by clinicians and researchers nowadays; however, there is limited evidence to date that improper positioning affects the mental state. Accordingly, the main objective of this research was to examine the impact of slump posture on mental fatigue and task performance. A sample of 60 participants, 30 in each group including those with normal and slump postures were recruited to perform an hour of typing on the computer. Mental fatigue through EEG and task performances were considered as outcome measures and then were analyzed statistically in the first and last 3 min of typing. The EEG showed a significant increasing trend in theta rhythm at different brain regions during 60 min of typing (P < 0.05). Besides, an interaction between time and posture was observed; it can mean the increasing trend of theta rhythm is different in normal and slump posture acquired sets (P < 0.05). Interestingly the speed of typing was found to be better (P < 0.05) in the normal posture group while no difference found between the groups in terms of errors (P > 0.05). Our results showed poor posture can induce more mental fatigue during the given task, than the normal posture. These findings have provided evidence to indicate that in addition to the peripheral and biomechanical component, the assessment of the cortex as the central component should be considered in poor posture individuals. Besides, for any possible physical therapy rehabilitation protocol for the management of poor posture, the peripheral and central components should be focused. Registered on the Iranian Registry of Clinical Trials on September 21, 2022, IRCT Identifier: IRCT20161026030516N2.